miR-198 targets TOPORS: implications for oral squamous cell carcinoma pathogenesis - Kaushik, Pankhuri; Mishra, Radha; Gopal, Champaka; Kumar, Arun (Frontiers in Oncology, 2024)
BackgroundmiRNAs play a critical role in the progression of various diseases, including oral squamous cell carcinoma (OSCC), which represents a major health concern and is one of the leading causes for new cancer cases worldwide. The miRNA dysregulation causes havoc and could be attributed to various factors, with epigenetic silencing of tumor suppressor genes being a major contributor to tumorigenesis. In this study, we have explored the tumor suppressive role of miR-198 in OSCC.MethodsThe tumor suppressive effect of miR-198 is established using miRNA analysis in OSCC cell lines, patient samples and xenograft nude mice model. The relationship between the miR-198 and TOPORS is explored using bioinformatics analyses, qRT-PCR, dual-luciferase reporter assay, Western blotting and cancer hall marks assays. The hypermethylation of the MIR198 promoter is confirmed using bisulfite sequencing PCR.ResultsWe have found miR-198 to be upregulated in OSCC cells treated with 5-Azacytidine, a known DNA methyltransferase inhibitor. Upregulation of miR-198 in 5-Azacytidine treated OSCC cells appears to be due to methylation of the MIR198 promoter. Using bioinformatics analysis and dual-luciferase reporter assay, we have identified TOPORS (TOP1 binding arginine/serine rich protein, E3 ubiquitin ligase) as a novel gene target for miR-198. miR-198-mediated repression of TOPORS decreases cell proliferation and anchorage-independent growth and enhances apoptosis of OSCC cells, which is dependent on the presence of the 3′UTR in TOPORS. An inverse correlation between the expression levels of miR-198 and TOPORS is observed in OSCC patient samples, highlighting the biological relevance of their interaction. Delivery of a synthetic miR-198 mimic to OSCC cells results in a significant decrease in xenograft size in nude mice, potentiating its use in therapeutics.ConclusionsThese results suggest that miR-198 is epigenetically silenced in OSCC, which promotes tumor growth, in part, by upregulating the levels of TOPORS.